أسلوب الدورية اليومية لترقية مهارة كتابة اللغة العربية - Zahro, Ahmad; Thohir, Muhammad; Ahsaniyah, Ivadatul; Alkhindi, Muhammad Umar Zaid (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Writing skill is the highest and most difficult skill when compared to other skills in Arabic. This skill is a skill with a high level of difficulty. However, writing skill is a very important skill in every learning process. This writing skill is an Arabic skill that has the ability to make students able to write well. In fact, the writing skills possessed by each student are different from one another. Sometimes they are able to write well but sometimes some of them have not been able to write well This is due to their lack of interest in learning Arabic, especially writing skills. This is triggered by the lack of appropriate learning techniques used. Therefore, to provide them with convenience In an effort to improve their writing skills, researchers use the daily journaling technique, which is the practice of selecting or recording on a paper (or pages in a journal) a collection of thoughts, understandings, and explanations of an idea or concept. The purpose of this research is to determine the students' writing skills and the application of daily journaling techniques to students and to determine the effectiveness of the application of daily journaling techniques to these students. The method used by the researcher in this study is a quantitative method, namely the use of methods with a deductive-inductive approach. While the data collection methods used by researchers in this study are observation, interviews, documentation and tests. The results obtained from this study are that after the application of the technique daily journals, students' writing skills increased by 59.1% and the number of students. The effectiveness of the application of daily journaling techniques to improve students' writing skills is significant with a value of 0.6890.